2022
DOI: 10.1039/d1dt04003k
|View full text |Cite
|
Sign up to set email alerts
|

A visible-light and temperature responsive host–guest system: the photoisomerization and inclusion complex formation of a ruthenium complex with cyclodextrins

Abstract: In the present study, we investigated the visible-light- and thermal-stimuli-responsive properties of a host–guest system based on proximal- and distal-[Ru(C10tpy)(C10pyqu)OH2]2+ (proximal and distal-1, C10tpy = 4’-decyloxy-2,2’;6’,2”-terpyridine, C10pyqu = 2-[2’-(6’-decyloxy)-pyridyl]quinoline). The...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…As reported previously, proximal - 1 photoisomerizes to distal - 1 to yield a mixture of the two isomers in the photostationary state. Furthermore, 1 H NMR measurements have shown that distal - 1 undergoes thermal back-isomerization to proximal - 1 at ambient temperature. , Absorption spectra during the thermal back-reaction using an aqueous solution of proximal - 1 and distal - 1 in the photostationary state are shown in Figure S6. The observed rate constant for spectral changes is 3.96 ± 0.03× 10 –5 s –1 , which is near-identical to the value obtained from 1 H NMR spectroscopy (4.0 × 10 –5 s –1 ) at the same temperature (303 K).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As reported previously, proximal - 1 photoisomerizes to distal - 1 to yield a mixture of the two isomers in the photostationary state. Furthermore, 1 H NMR measurements have shown that distal - 1 undergoes thermal back-isomerization to proximal - 1 at ambient temperature. , Absorption spectra during the thermal back-reaction using an aqueous solution of proximal - 1 and distal - 1 in the photostationary state are shown in Figure S6. The observed rate constant for spectral changes is 3.96 ± 0.03× 10 –5 s –1 , which is near-identical to the value obtained from 1 H NMR spectroscopy (4.0 × 10 –5 s –1 ) at the same temperature (303 K).…”
Section: Resultsmentioning
confidence: 99%
“…Ruthenium complexes with polypyridyl ligands are promising candidates for the stimuli-responsive molecules. These complexes absorb visible light because of the metal-to-ligand charge-transfer (MLCT) transition, followed by fast relaxation of singlet excited states to triplet MLCT ( 3 MLCT) states via a radiationless intersystem crossing . The 3 MLCT excited states, which have submicrosecond lifetimes, have enabled applications in photoredox reactions, , artificial photosynthesis, and electrochemiluminescence .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations